(untitled) (Journal of Humanitarian and Applied Sciences, 2025)
Vehicular Ad-Hoc Networks (VANETs) constitute a specialized sub-class of Mobile Ad-Hoc Networks (MANETs) tailored for high-mobility vehicular environments, and serve as a critical enabler of intelligent transportation systems (ITS). This survey presents (Al-Sultan et al., 2014) the architectural and characteristic foundations of VANETs; (Hartenstein & Laberteaux, 2010) a systematic, comparative analysis of routing and dissemination protocol classes-including recent advancements incorporating machine learning, Software-Defined Networking (SDN) and edge-computing paradigms; and (Routing Protocols…, 2023) an overview of emerging technologies shaping VANET evolution, such as federated learning, digital twins, 5G/6G V2X, and trust-based security frameworks. Through objective evaluation across metrics such as packet delivery ratio, latency, scalability, overhead and adaptability, the paper identifies current limitations and sets out a roadmap toward next-generation AI-driven, data-centric vehicular communication networks.